ANALISA PENGENDALIAN PIUTANG UNTUK MEMINIMALKAN PIUTANG TAKTERTAGIH PADA PT. BANK CENTRAL ASIA TBK KCP LOKASARI - Imhar; Rini Maiyana (Pusat Riset dan Inovasi Nasional, 2022)
The role of Banks in a country is very important, because banks function as the economic development of a country. Almost all parties and sectors need banks for transactions, one of which is for savings and loans, KKB, KPR etc. The bank is called the creditor and the customer is called the debtor. In granting credit or bank debt, it must be able to cover all risks that will occur. There is a principle of prudence, one of which is that banks must take a more in-depth approach to the profile of prospective customers who will make transactions, either saving or making loans. The risk of a loan that cannot be paid by the customer is called bad debt. In this journal the author will share the results of research on the analysis of receivables control to minimize bad debts at the BCA KCP Lokasari bank so as not to burden the bank's overall operations.